EFFECT OF ORGANIC SELENIUM AND VITAMIN E ON SOME BLOOD AND BIOCHEMICAL PARAMETERS IN COMMON CARP CYPRINUS CARPIO L. - M. A. Mohammad; M. A. Hasan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The aim of this research is to add various quantities of organic selenium with or without α-tocopherol to support growth and reduce oxidative stress. A total of 168 fingerlings of common carp Cyprinus carpio with an average weight of 31±2 g/fish were distributed in 24 glass aquariums. Fish were fed on eight different experimental diets, including a control, and a diet that contains 0.6, 0.7 and 0.8 mg/kg of organic selenium (2nd, 3rd and 4th diets) respectively. The fifth, sixth and seventh diets contained the same amounts of organic selenium with 300 mg/kg of α-tocopherol, but only α-tocopherol was added to the eighth diets. The results of a statistical analysis found that the use of organic selenium with α-tocopherol enhanced the values of blood parameters included Hb and PCV which reached 10.85 gm/100 ml, 33.03% respectively; biochemical included TP, GLU and GPx which reached 4.13 g/100 ml, 2.08 mg/100 ml and 1.90 pg/ml respectively, while the control diets have 9.35, 27.80, 3.67, 84.50 and 1.34 respectively i.e., the eighth treatment (0.8 organic selenium with Vitamin E) representing the best treatments.